(untitled) (KULT_online, 2011)
In his dissertation Ercüment Çelik explores street trader organizing as the bridge between trade unions and social movements in contemporary South Africa. Based on the question of how street traders deal with their marginalization in the post-apartheid era, the author researches working conditions on the street and living conditions in shack settlements. The chosen perspective—that the spheres of work and community are not isolated phenomena of marginalization—reveals the innovative character of Çeliks study. The author shows moreover, that this combination lays the basis for an intensified cooperation between social movements and trade unions in South Africa.